Development of a Three-Dimensional Geometry Optimization Method for Turbomachinery Applications - Steffen Kämmerer; Jürgen F. Mayer; Heinz Stetter; Meinhard Paffrath; Utz Wever; Alexander R. Jung (International Journal of Rotating Machinery)
This article describes the development of a method for optimization of the geometry of three-dimensional turbine blades within a stage configuration. The method is based on flow simulations and gradient-based optimization techniques. This approach uses the fully parameterized blade geometry as variables for the optimization problem. Physical parameters such as stagger angle, stacking line, and chord length are part of the model. Constraints guarantee the requirements for cooling, casting, and machining of the blades.